(untitled) (Journal of actual problems of jurisprudence, 2018)
The article deals with problems of standardization as a way to ensure the quality of products, works and services, the definition of standardization. In considering this issue have been analyzed the views and opinions of some legal scholars, draw appropriate conclusions. Key words: standardization, quality, products, services, certificate.